Teachers’ Scaffolding Science Reading Comprehension in Low-Income Schools: How to Improve Achievement in Science - Rojas-Rojas, S (Routledge, 2019)
Reading is a tool that promotes the learning of science across schooling. Scientific texts are conceptually and linguistically complex, especially for students from low-income contexts because they have neither the experience with the language nor the literacy skills to face the challenges of scientific knowledge. This study used a mix method approach to compare the cognitive scaffolding practiced by teachers during science reading activities in high- and low-performing schools. Three teachers and 141 fourth grade students from low socioeconomic background schools participated in 48 class sessions. Classes were video-recorded and transcribed. The data were analyzed using Sanchez’ Pedagogic Practice Analysis System. The results show that teachers from both types of schools continuously use reading as a tool for learning. The effective teacher uses reading with non-invasive scaffolding and varied verbal participation to elaborate knowledge, promoting literal and inferential comprehension and more opportunities for the students to construct knowledge. By contrast, less effective teachers use reading with invasive scaffolding and little verbal participation of the students to consolidate knowledge, promoting mainly literal comprehension. This study shed light on different approaches teachers use to foster reading comprehension for science learning. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.